Smart tags based on the batteryless backscatter technology:applications and challenges - Ying GUO; Gongpu WANG; Zonghui LI; Ruisi HE; Zhangdui ZHONG (物联网学报)
Since the radio frequency identification (RFID) technology was put forward,it has been widely used in the transportation,logistics,industry and business due to its convenience and high efficiency.As a carrier for storing recognizable data,the RFID tags play a crucial role in the Internet of things (IoT).More and more functions and modules are embedded in the RFID tags and developed into smart tags in different application fields.Recently,wireless batteryless smart tags have arisen and grown rapidly with the development of the IoT and various emerging backscatter technologies.Wireless batteryless smart tags use the passive backscatter technology to harvest the energy and transmit information through radio frequency signals.Starting from the RFID technology,the history of the RFID and smart tags was introduced briefly,the differences between traditional smart tags and emerging wireless smart tags were compared,the advantages of wireless batteryless smart tags were concluded,several specific applications of it in different fields were listed,and the open challenges were analyzed.